A Case of Postsurgical Necrotizing Fasciitis Invading the Rectus Abdominis Muscle and Review of the Literature - Francesco Carbonetti; Antonio Cremona; Marco Guidi; Valentina Carusi (Case Reports in Medicine)
Necrotizing fasciitis is a life-threatening, soft tissue infection and an early diagnosis is needed to permit a prompt surgical and medical intervention. Due to the high fatal potential of the disease complications, the radiologist should distinguish necrotizing fasciitis from the most common soft tissue infections, in order to permit a prompt surgical and medical treatment. We present a case of a wide necrotizing fasciitis who presented at our emergency department and we also provide the basic tools, through a review of the literature, for the general radiologist to distinguish, with computed tomography and magnetic resonance imaging, necrotizing fasciitis from the most common infections that could present during our routine practice.